2017
DOI: 10.1021/acs.orglett.7b00471
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Enantioenriched γ-Amino-α,β-unsaturated Esters Utilizing Palladium-Catalyzed Rearrangement of Allylic Carbamates for Direct Application to Formal [3 + 2] Cycloaddition

Abstract: An efficient synthesis of enantioenriched γ-amino-α,β-unsaturated esters was developed by utilizing the palladium-catalyzed decarboxylative rearrangement of enantioenriched allylic carbamates possessing an ester moiety at the allylic position. The reaction proceeded in good yield with a high degree of chirality transfer by making use of Xantphos as a superior ligand for the catalyst. The products directly participated in the formal [3 + 2] cycloaddition reaction with tosyl isocyanate under Brønsted base cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Moreover, we used insertion products 7n and 7t to synthesize bioactive compounds (Scheme C). Specifically, cannabinoid receptor 1 inhibitor 18 , which has a pyrrolidin-2-one core structure, was prepared from 7n by means of an allylic rearrangement–cyclization sequence (eqs e and f), demonstrating the potential utility of our protocol for the synthesis of important chiral pyrrolidin-2-ones . In addition, a formal synthesis of the chiral drug sertraline was realized by subjecting 7n to a palladium-catalyzed stereospecific allylic arylation (eq g) .…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, we used insertion products 7n and 7t to synthesize bioactive compounds (Scheme C). Specifically, cannabinoid receptor 1 inhibitor 18 , which has a pyrrolidin-2-one core structure, was prepared from 7n by means of an allylic rearrangement–cyclization sequence (eqs e and f), demonstrating the potential utility of our protocol for the synthesis of important chiral pyrrolidin-2-ones . In addition, a formal synthesis of the chiral drug sertraline was realized by subjecting 7n to a palladium-catalyzed stereospecific allylic arylation (eq g) .…”
Section: Resultsmentioning
confidence: 96%
“…In the case of the palladium‐catalyzed transformation, the boron species is attempted to be essential for both the epoxide activation [41a] and the regioselectivity of the amine addition, as depicted in Scheme 5b. As an alternative, Terada recently established a palladium‐catalyzed decarboxylative rearrangement of enantioenriched allylic carbamates to prepare chiral γ‐amino‐α,β‐unsaturated esters (Scheme 5d) [41b] …”
Section: Chemical Route To Vinylogous and Heteroaromatic γ‐Amino Acidsmentioning
confidence: 99%
“…The aza-Michael strategy was also applied in the synthesis of enantioenriched β,γ-diamino acid derived imidazolidin-2-ones by Terada [179]. γ-Amino-α,β-unsaturated esters were caused to react with tosyl isocyanates in a formal [3 + 2] cycloaddition using 10% of DIPEA as the catalyst.…”
Section: Catalysts 2018 8 X For Peer Reviewmentioning
confidence: 99%
“…A similar approach was applied to the desymmetrization of cyclohexadienones with isocyanates in presence of a catalytic amount of DBU (1,8-Diazabicyclo(5.4.0)undec-7-ene) [179]. The authors reported the synthesis of a broad range of bicyclic imidazolidin-2-ones with high diastereomeric ratios (Scheme 63).…”
Section: Catalysts 2018 8 X For Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation